Design, Synthesis, and Anti-mycobacterial Evaluation of New 3,5-Disubstituted-pyrazole-1-carbothioamides - Kok Tong Wong; Hasnah Osman; Thaigarajan Parumasivam; Muhammad Solehin Abd Ghani; Unang Supratman; Mohamad Nurul Azmi Mohamad Taib; Mohd. Zaheen Hassan (Universitas Gadjah Mada, 2022)
Two series of new 3,5-disubstituted-pyrazole-1-carbothioamides (4a-f and 5a-e) were designed and synthesized through condensation reaction between chalcones and thiosemicarbazides under alkaline condition via cyclocondensation reaction. The structures have been elucidated by Fourier-transform infrared (FTIR), High-resolution mass spectrometry (HRMS), one- and two-dimensional nuclear magnetic resonance (NMR) analyses. These compounds were assayed for in vitro anti-tuberculosis activity against Mycobacterium tuberculosis H37Ra using the Tetrazolium microplate assay (TEMA) method. As a result, six compounds (i.e., 4a, 4d, 4f, 5a, 5c, and 5d) showed a weak activity with minimum inhibition concentration (MIC) between 650–530 μM, and other compounds showed no inhibition against MTB. In addition, all tested compounds also did not show any cidal effects for minimum bactericidal concentration (MBC), even at the highest test concentration.